A cohesive premixed monetite biocement. Issue 3 (30th December 2016) - Cox, Sophie C.; Patel, Sarika; Gbureck, Uwe; Wright, Adrian J.; Grover, Liam M.
Abstract: Sodium alginate was successfully utilized to improve cohesion and limit particulate debris of a premixed calcium phosphate cement (pCPC) that following the exchange of water set to form monetite. Modified pastes using glycerol and 2 wt% alginate exhibited initial and final setting times of 60 ± 9 and 1355 ± 105 minutes, respectively. Despite these setting times being significantly longer than clinically recommended the improved washout resistance of this formulation would allow for wound closure during setting. Set monetite pastes exhibited a maximum compressive strength of 8.6 ± 3.5 MPa with a corresponding porosity of 59% compared to 15.6 ± 5.8 MPa and 25% for the unmodified aqueous brushite cement. Storage of the pCPC paste at 4°C for 14 days was shown to significantly ( P <0.05) increase the compressive strength of the harden matrix (13.2 ± 1.5 MPa), however, subsequent deterioration was observed after 90 days storage. Methylene blue was utilized to visualize perfusion into the matrix during setting, demonstrating that the use of glycerol altered mass transport and ultimately shifted the crystallization kinetics in favor of monetite. Samples >20 mm did not reach full saturation after 10 days of immersion, which for the first time suggests an upper volume limit that will form a homogeneous cement highlighting an important consideration for clinical translation of pCPCs.